Management of Recurrent Skin Dehiscence by Subcutaneous Ureteral Bypass Shunting Port in a Bitch - Efficacy of Doxycycline - Yun, Jongchul; Lee, Sungin (Acta Scientiae Veterinariae, 2025)
Background: Ureteral obstruction compromises renal function depending on duration, requiring immediate evaluation and renal decompression. Less invasive interventional techniques increasingly supplement traditional surgical treatments. In dogs, double pigtail ureteral stents are commonly used; however, subcutaneous ureteral bypass devices should be treatment options when stents fail due to complications. Doxycycline, a tetracycline antibiotic, has been shown to have anti-inflammatory and immunomodulatory properties by various mechanisms. This report demonstrates the efficacy of doxycycline for managing recurrent skin dehiscence caused by a local immune response to a SUB shunting port in a bitch. Case: A 10-year-old spayed bitch toy poodle weighing 4.1 kg, was referred for recurrent skin dehiscence at the SUB shunting port placement site. The bitch had been diagnosed with right ureteral obstruction caused by a ureteral calculus 15 months ago, and unilateral SUB placement had been performed. The animal underwent 3 reconstructive surgeries with broad-spectrum antibiotics treatment at the local animal hospital. Despite these interventions, skin dehiscence recurred at the SUB shunting port placement site. On presentation, the shunting port was exposed on the right side of the midline, with a mild exudate around the port. Cytology examination and bacterial culture were negative for infection. Laboratory tests revealed elevated blood urea nitrogen, alkaline phosphatase, C-reactive protein, and monocytosis. Diagnostic imaging showed severely irregular margins of both kidneys, bilateral renal and right ureteral calculi, with the SUB device correctly placed and no evidence of fluid leakage or displacement. Based on the patient’s history and these findings, the skin dehiscence was determined to be caused by a local immune response. Treatment with doxycycline, known for its anti-inflammatory and immunomodulatory effects, was selected. SUB replacement with skin debridement was performed under general anesthesia, and doxycycline was administered orally for 4 weeks. At the 3-week post-surgery follow-up, the skin had completely healed, demonstrating the successful treatment outcome. At 3 months post-surgery, no complications were observed, and the overall condition remained stable. Discussion: To our knowledge, this is the 1st report of recurrent skin dehiscence caused by a subcutaneous ureteral bypass shunting port. The implantation of medical devices triggers a complex signaling cascade with the host’s immune system, resulting in foreign body reactions. The lack of response to previous antibiotic treatments at the local animal hospital, the absence of bacterial infection evidence, and the clinical improvement with doxycycline suggest that the immune and inflammatory response to the medical device was modulated through mechanisms such as matrix metalloproteinase inhibition, decreased pro-inflammatory cytokine levels, and reduced reactive oxygen species. Although these complications with subcutaneous ureteral bypass devices are rare, immune responses should be considered in cases of poor response to treatments. These foreign body reactions are highly complex, and their mechanisms are not fully understood, making diagnosis and treatment challenging. Since the limited therapeutic options available to mitigate these responses with minimal adverse effects, doxycycline presents a viable alternative for managing complications associated with medical devices in dogs. Keywords: canine, dog, ureteral obstruction, subcutaneous ureteral bypass, skin dehiscence, doxycycline, immunomodulatory agent.